Food and beverage selection in children's sports arenas in Norway: a cross-sectional study - Lisa Garnweidner-Holme; Yngvild Frivold; Gigja Max; Kristin Fjæra; Therese Fostervold Mathisen; Mari Charlotte Wik Myhrstad (Cambridge University Press, 2024)
Abstract Objective: To assess the selection of foods and beverages in children's sports arenas in Norway. Design: A cross-sectional study design with a digital questionnaire was used. Descriptive statistics were used to present the results. Moreover, Pearson's χ 2 tests examined the factors that could aid in distinguishing clubs with healthy or unhealthy consumables. Setting: Children's sports clubs in Norway. Participants: Representatives from 301 children's sports clubs in Norway answered the questionnaire between September and November 2021. Results: In total, 89·4% of the participating sports clubs (n 301) offered soda drinks with sugar. Most of the sports clubs (88 %) reported to offer batter-based cakes such as pancakes and waffles and 63·8 % offered cakes. Furthermore, 47·5% sold hot dishes with processed meat, such as hamburgers and hot dogs. More than 80% of the sports clubs offered sweets and snacks, while 44·5% did not offer fruits, vegetables and/or berries. Notably, the important factors that distinguished sports clubs with healthier food selections from those with unhealthier selections were the presence of guidelines for the food offered and purchase agreements with food suppliers. Conclusions: Educational, governmental guidelines for the promotion of healthy eating and establishing agreements with suppliers of healthier foods could help to overcome barriers to unhealthy food selection.